L’alcool au volant, c’est criminel depuis 1921 ! - Landreville, Pierre; Lavergne, Chantal (Criminologie, 1989)
Bill C-51 passed by the Canadian Parliament in 1985 and the publicity surrounding this legislation led many people to believe that a new crime regarding impaired driving had been created. This Bill, however, was to simply increase the penalty for drunk driving in the case of a first conviction. In fact, the penal solution to the “problem” of drunk driving is not new; in 1921 the offence of impaired driving was first introduced into the Code. This article examines the evolution of the prohibition of driving under the influence of alcohol in the Canadian Criminal Code and the enforcement of this law in Canada, in Quebec and in Ontario from 1921 to 1973. The first part presents the evolution of legislation concerning impaired driving. It goes through six important phases and covers the period from 1921 to 1973. The second part presents the statistical data used in our study. We also consider the reliability and validity of the data used. In the last part, we analyze the implementation of the law on infractions relating to drunk driving in a state of drunkeness indictable offence and summary conviction offence driving under the influence of alcohol or a drug (indictable offence and summary conviction offence), and finally, refusal to furnish a sample of breath (summary conviction offence). In conclusion, we present several recommendations based on the results of our analysis.